A Multi-camera, Multi-projector Super-Resolution Framework for Structured Light - Weinmann, M.; Schwartz, C.; Ruiters, R.; Klein, R. (2011 International Conference on 3D Imaging, Modeling, Processing, Visualization and Transmission, 2011)
In this work, we present a framework for multi-camera, multi-projector object acquisition based on structured light. This approach allows the reconstruction of an object without moving either the object or the acquisition setup, avoiding any registration of independent measurements. To overcome the resolution limitations of the individual projectors, we introduce a novel super-resolution scheme. By exploiting high dynamic range imaging, we are able to handle even complicated objects, exhibiting strong specularities. We show that, combined with an iterated bundle adjustment, these improvements increase the accuracy of the obtained point cloud.